Split‐Attention and Coherence Principles in Multimedia Instruction Can Rescue Performance for Learners with Lower Working Memory Capacity. Issue 5 (16th June 2016) - Fenesi, Barbara; Kramer, Emily; Kim, Joseph A.
Summary: This study examined the relation between working memory capacity (WMC) and the principles of Split‐Attention (Experiment 1) and Coherence (Experiment 2) in multimedia learning. Split‐Attention refers to reduced comprehension when learners must divide their attention between images and text, and Coherence refers to reduced comprehension when learners must process irrelevant information. In Experiment 1, those with lower WMC performed worse compared with those with higher WMC when learning from the Split‐Attention condition (audio + on‐screen text + images), but not when learning from the Complementary condition (audio + images). In Experiment 2, those with lower WMC performed worse compared with those with higher WMC when learning from the Incongruent condition (audio + irrelevant images), but not when learning from the Congruent condition (audio + relevant images). Findings reinforce the importance of pedagogically sound instructional design, as it may especially benefit those with lower WMC and equate learning across working memory abilities. Copyright © 2016 John Wiley & Sons, Ltd.